Cataract surgery in myopic eyes. Issue 1 (24th January 2023) - Elhusseiny, Abdelrahman M.; Salim, Sarwat
Abstract : Purpose of review: We discuss the preoperative, intraoperative, and postoperative considerations for cataract surgery in eyes with high myopia. We also reviewed the recent literature on refractive outcomes and complications of cataract surgery in myopic eyes. Recent findings: Several novel intraocular lens (IOL) power calculation formulas have recently been developed to optimize refractive outcomes. Haigis formula is the most accurate among the third-generation IOL formulas. Novel formulas such as Barrett Universal II, Kane, and modified Wang-Koch adjustment for Holladay I formula provide a better refractive prediction compared with old formulas. Intraoperatively, the chopping technique is preferred to minimize pressure on weak zonules and reduce the incidence of posterior capsule rupture. Anterior capsular polishing is recommended to reduce the risk of postoperative capsular contraction syndrome (CCS). Postoperatively, complications such as refractive surprises, intraocular pressure spikes, and CCS remain higher in myopic eyes. Only 63% of myopic patients with axial length more than 26 mm achieve a visual acuity at least 20/40 after cataract surgery, mainly because of coexisting ocular comorbidities. Summary: There are multiple preoperative, intraoperative, and postoperative considerations when performing cataract surgery in myopic eyes. Further research is needed to optimize the refractive outcomes in these eyes and determine the best IOL formula. Surgeons should be adept and knowledgeable with different techniques to manage intraoperative complications.